2015
DOI: 10.4067/s0718-58392015000100004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of faba bean genotypes with Orobanche foetida Poir. and Orobanche crenata Forsk. infestation in Tunisia

Abstract: Orobanche foetida Poir. and O. crenata Forsk. are major constraints to faba bean (Vicia faba L.) cultivation in Tunisia. To evaluate the different levels of resistance of seven small-seeded faba bean genotypes to these parasitic weed species, three trials were conducted in fields infested and non-infested with O. foetida in the Oued Beja Agricultural Experimental Unit and O. crenata in an experimental field at Ariana of the National Institute of Agricultural Research during three cropping seasons. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
(24 reference statements)
4
19
0
Order By: Relevance
“…These results show that Giza-843 variety was more tolerant to Orobanche crenata infestation which positively reflected the accumulation of dry materials plant -1 than Giza-2 variety during reproductive stage. These results are in the same context with those obtained by Trabelsi et al (2015), who found the parasitism index on the new faba bean genotypes varied from 2-6 times less than susceptible 'Badï'. …”
supporting
confidence: 78%
“…These results show that Giza-843 variety was more tolerant to Orobanche crenata infestation which positively reflected the accumulation of dry materials plant -1 than Giza-2 variety during reproductive stage. These results are in the same context with those obtained by Trabelsi et al (2015), who found the parasitism index on the new faba bean genotypes varied from 2-6 times less than susceptible 'Badï'. …”
supporting
confidence: 78%
“…Results showed that the seven tested breeding lines, except L5, showed good resistance level to O. foetida that was expressed by a low parasitism severity and number of emerged Orobanche spikes. The breeding line L5 appeared to behave differently compared to previous results showed by Trabelsi et al (2015). This can be explained by the influence of cultural and climatic conditions as indicated by several authors (Maalouf et al, 2011;.…”
Section: Discussionmentioning
confidence: 65%
“…Breeding for resistance to broomrapes in faba bean against O. crenata (Rubiales et al, 2014;Trabelsi et al, 2015) was well studied. Rubiales et al (2014) summarized the work conduced in legume breeding for broomrape resistance.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Soliman et al (2012) found that the highest yielding ability under heavy broomrape infestation was shown by the F4 selection of three crosses involving the most resistant parental cultivar "Giza843" with a mean seed yield per plant of 60 g. Zakaria et al (2016) proved that shoot dry weight, root weight, shoot length and root length traits significantly increased under heavily natural infested soil with O. crenata seeds in the broomrape-tolerant genotypes ("Misr1" and "FAB476") while the volume of root size and number of haustoria of faba bean plants traits were significantly increased in the broomrapesusceptible genotypes ("Karra", "Nubaria1", "FAB124" and "Vattholoma"). The same criteria was reported by Trabelsi et al (2015) where they studied performance of faba bean genotypes with O. foetida Poir and O. crenata (Forsk) infestation in Tunisia.…”
Section: Least Significant Differences (Lsd) Among Genotypesmentioning
confidence: 82%